Neonatal Overnutrition Increases Testicular Size and Expression of Luteinizing Hormone β-Subunit in Peripubertal Male Rats - Argente-Arizón, Pilar; Castro-González, David; Díaz, Francisca; Fernández-Gómez, María J.; Sánchez-Garrido, Miguel A.; Tena-Sempere, Manuel; Argente, Jesús; Chowen, Julie A. (Frontiers in Endocrinology, 2018)
Proper nutrition is important for growth and development. Maturation of the reproductive axis and the timing of pubertal onset can be delayed when insufficient nutrition is available, or possibly advanced with nutritional abundance. The childhood obesity epidemic has been linked to a secular trend in advanced puberty in some populations. The increase in circulating leptin that occurs in association with obesity has been suggested to act as a signal that an adequate nutritional status exists for puberty to occur, allowing activation of central mechanisms. However, obesity-associated hyperleptinemia is linked to decreased leptin sensitivity, at least in adults. Here we analyzed whether neonatal overnutrition modifies the response to an increase in leptin in peripubertal male rats, as previously demonstrated in females. Wistar rats were raised in litters of 4 (neonatal overnutrition) or 12 pups (controls) per dam. Leptin was administered sc (3 μg/g body weight) at postnatal day (PND) 35 and the rats killed 45 minutes or 2 hours later. Postnatal overfeeding resulted in increased body weight and circulating leptin levels; however, we found no overweight-related changes in the mRNA levels of neuropeptides involved in metabolism or reproduction. In contrast, pituitary expression of luteinizing hormone (LH) beta-subunit was increased in overweight rats, as was testicular weight. There were no basal differences between L4 and L12 males or in their response to leptin administration in pSTAT3 levels in the hypothalamus at either 45 min or 2 h. In contrast, pJAK2 was found to be higher at 45 min in L4 compared to L12 males regardless of leptin treatment, while at 2 h it was higher in L4 leptin treated males compared to L12 leptin treated males, as well as L4 vehicle treated rats. There were no changes in response to leptin administration in the expression of the neuropeptides analyzed. However, serum LH levels rose only in L4 males in response to leptin, but with no change in testosterone levels. In conclusion, the advancement in pubertal onset in males with neonatal overnutrition does not appear to be related to overt modifications in the central response to exogenous leptin during the peripubertal period.